Efficacy of phosphate solubilizing microorganisms in utilizing native phosphorus in an alkaline alluvial soil of North India - ALAM, KHURSHID; BARMAN, MANDIRA; DATTA, SIBA PRASAD; KUMAR, SARVENDRA; ANNAPURNA, K; SHUKLA, LIVLEEN; CHAKRABORTY, DEBASHIS (The Indian Journal of Agricultural Sciences, 2020)
Utilization of phosphate solubilizing microorganisms (PSMs) to solubilize the fixed P pool in soil is a promising method considering the shrinking availability of raw material (rock phosphate) of phosphatic fertilizer production in one hand and global food security on the other. An incubation study was carried out for 90 days to assess the ability of the two PSMs, namely Enterobacter sp. and Aspergillus niger in mediating the release of P from fixed pool in an alluvial soil (pH= 8.30) of IARI farm, New Delhi. On an average, both the microorganisms significantly increased the release of P into solution from fixed P pool of soil. However, Enterobacter sp. treated soil showed better P release (0.52 mg/kg) than that of Aspergillus niger treated soil (0.44 mg/kg) over uninoculated control (0.42 mg/kg). Enterobacter sp. was capable in mediating P release into soil solution during the whole period of incubation. Soil treated with Enterobacter sp. showed almost similar level of solution P concentration from 2nd week to 6th week of incubation and after that, there was a decrease. Whereas, A. niger was able to mediate P release into soil solution only up to 28 days of incubation, after that solution P concentration of treated soil became statistically at par with untreated control. Thus, Enterobacter sp. performed better than A. niger in utilizing native P in alluvial soil.